Comparisons of typical nonlinear states in single- and dual-beam optically injected semiconductor lasers - Qi, Xiaoqiong; Xie, Liang; Liu, Yuping (Optics communications, 2013)
The characteristics of the typical nonlinear states in an optically injected laser system with single- and dual-beam injection are analyzed and compared numerically. Both single- and dual-beam optical injection systems can generate periodic oscillations and chaos states but with different characteristics. By observing the evolution process of periodic oscillations, it is found that dual-beam injection induced periodic oscillations have multiple time series patterns including continuous periodic signals with single peak (CPS) and continuous periodic signals with subharmonic (CPSSH), while for single-beam injection with either of the dual-beam injection parameters generated periodic oscillations, the extremum numbers of the time series equal to the frequency period numbers of the optical spectrum. In addition, the great advantages of bandwidth enhancement effect for chaos oscillations are obtained by using dual-beam injection. Furthermore, extensive numerical simulations reveal that dual-beam injection system undergoes period-doubling routes to chaos, which is identical to that in single-beam injection system. Finally, the characteristics of newly clustered NDFWM dynamics in dual-beam injection system are analyzed.